2014
DOI: 10.3892/or.2014.3524
|View full text |Cite
|
Sign up to set email alerts
|

RUNX3 is inactivated by promoter hypermethylation in malignant transformation of ovarian endometriosis

Abstract: Abstract. The aim of the present study was to investigate the role of epigenetic inactivation of the runt-related transcription factor 3 gene (RUNX3) in the malignant transformation of ovarian endometriosis. Samples obtained by microdissection and scraping included 30 malignant ovarian endometriotic cyst tissues and 30 corresponding eutopic endometrium tissues from the endometriosis-associated ovarian carcinoma (EAOC) group, 19 benign ovarian endometriotic cyst tissues and 22 corresponding eutopic endometrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Interestingly, methylation levels of these two sites were correlated with each other (r=0.822, p<0.001) However, only the degree of methylation at the transcription start had a direct correlation with lower RUNX3 expression (r=−0.429, p=0.029) (see online supplementary table S2). We did not observe a difference in methylation patterns between men and women (data not shown); this is noteworthy since oestrogen has been suggested to be able to regulate RUNX3 methylation patterns 23. Next, we isolated pDCs from patients with SSc and cultured them in the presence of demethylating agent 5-Aza-CdR (figure 2C).…”
Section: Resultsmentioning
confidence: 75%
“…Interestingly, methylation levels of these two sites were correlated with each other (r=0.822, p<0.001) However, only the degree of methylation at the transcription start had a direct correlation with lower RUNX3 expression (r=−0.429, p=0.029) (see online supplementary table S2). We did not observe a difference in methylation patterns between men and women (data not shown); this is noteworthy since oestrogen has been suggested to be able to regulate RUNX3 methylation patterns 23. Next, we isolated pDCs from patients with SSc and cultured them in the presence of demethylating agent 5-Aza-CdR (figure 2C).…”
Section: Resultsmentioning
confidence: 75%
“…Paralleling RUNX1, RUNX2 is hypomethylated in post-CT samples from HGSOC patients [75] and a correlation between RUNX2 overexpression, tumour progression and poor disease diagnosis in ovarian cancer has been described [135]. Contradictory evidence of both a tumour suppressor and a tumour promoter has been reported for RUNX3, which is hypermethylated [136,137], as well as overexpressed [138] in ovarian cancer. In terms of the uterus, Runx3, like Runx1, may have a role in the normal physiology of the organ [134], but unlike the pro-oncogenic properties of RUNX1 (see above), it seems that inactivation of RUNX3 is linked to endometrial carcinoma [139].…”
Section: The Runx1 'Siblings' In Female-related Cancersmentioning
confidence: 93%
“…The runt-related transcription factor 3 gene ( RUNX3 ) has been shown to be a tumour suppressor in a variety of cancers. Guo et al recently reported that the inactivation of the RUNX3 gene by promoter hypermethylation plays a role in the malignant transformation of ovarian endometriosis and is closely related to estrogen metabolism ( 117 ). The tumour suppressor gene, Ras-association domain family member 2 ( RASSF2 ), is inactivated by promoter hypermethylation in many types of cancer ( 118 120 ).…”
Section: Malignant Transformation Of Endometriosismentioning
confidence: 99%